Emily Dickinson and the question of 'giving death'. Issue 10 (26th November 2019) - Cazé, Antoine
ABSTRACT: This article examines Emily Dickinson's 'difficult projects of thinking' (Deppman), and more particularly her idiosyncratic approach to death, through the reading of one famous poem – 'It was not Death, for I stood up'. I argue that, by defining death negatively, this poem sets the stage for a thought experiment, allowing the poet to explore the difficulties inherent in any act of thinking. In an initial step, I review various critical evaluations of Dickinson's commitment to philosophical issues, showing how the form of the lyric had a major impact on her understanding how to deal with these issues. When seeking for poetic advice from Thomas W. Higginson in 1862, Dickinson crucially wondered if her 'verse' was 'alive': for her, writing poetry and thinking radically were a question of life and death – a question I examine through the prism of Jacques Derrida's essay, The Gift of Death ( Donner la mort ). In a culture still ruled by Calvinist doctrines, how can one have a practice of death, as not only a spiritual exercise, but also a philosophical one?